2020
DOI: 10.24925/turjaf.v8i3.733-740.3256
|View full text |Cite
|
Sign up to set email alerts
|

Floristic Patterns and Qualities of Forage Species from Mountainous Rangeland in the Middle Black Sea Region of Turkey

Abstract: This study was carried out to investigate the floristic features (family, preference by grazers, growth form and response to grazing) and qualities of forage species collected from mountainous rangeland (Akdağ Mountain, Ladik) in the middle Black Sea region of Turkey. Forage samples were collected five times by 15-day intervals from the before-flowering stage to the after-flowering stage in 2015 and 2016. The total number of species was 105 species belonging to 73 genera and related to 26 families. Of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Indeed, burr medic genotypes with autumn-spring cycles can constitute the most productive part of forage resources by covering grazing area or crop field, if even at a relatively short duration (Del Pozo et al, 2002;Iannucci et al, 2008;Crews et al, 2016). Annual reseeding medics provide an abundance of fresh forage with , 2, 8, 13, 17, 24, 25, 26, 28, 31, 39, 40 and 43), Medium-flowering burr medic genotypes (3, 5, 9, 11, 12, 29, 30, 33, 36, 37, 42 and 44), Late-flowering burr medic genotypes (4, 6, 7, 10, 14, 15, 16, 18, 19, 20, 21, 22, 23, 27, 32, 34, 35, 38 and 41) high nutritive value during the spring, summer, and fall seasons (Uzun and Ocak, 2019) and thus diminish the negative implications of grazing animals on desirable perennial species (Aydin et al, 2020). Furthermore, the reported results and suggested genotypes based on their nutritional relationships can be further utilized in breeding programs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, burr medic genotypes with autumn-spring cycles can constitute the most productive part of forage resources by covering grazing area or crop field, if even at a relatively short duration (Del Pozo et al, 2002;Iannucci et al, 2008;Crews et al, 2016). Annual reseeding medics provide an abundance of fresh forage with , 2, 8, 13, 17, 24, 25, 26, 28, 31, 39, 40 and 43), Medium-flowering burr medic genotypes (3, 5, 9, 11, 12, 29, 30, 33, 36, 37, 42 and 44), Late-flowering burr medic genotypes (4, 6, 7, 10, 14, 15, 16, 18, 19, 20, 21, 22, 23, 27, 32, 34, 35, 38 and 41) high nutritive value during the spring, summer, and fall seasons (Uzun and Ocak, 2019) and thus diminish the negative implications of grazing animals on desirable perennial species (Aydin et al, 2020). Furthermore, the reported results and suggested genotypes based on their nutritional relationships can be further utilized in breeding programs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, desirable annual and perennial legumes offer essential opportunities for sustainable rangelandbased animal production. These forages contribute to animal production by increasing the yield and nutritional value of rangeland and field crops and raising the conversion efficiency of herbage to animal protein (Lüscher et al, 2014;Uzun and Ocak, 2019;Aydin et al, 2020). Researchers have to improve the quality and yield of legumes using advances in plant breeding to increase their contributions to both grazing and ley farming systems.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted as part of the major research project (TOVAG -214O228), namely "Experiments on development of quality index in forage crops based on relative forage quality (RFQ)". In this study, we evaluated 21 weed species, the most dominant species (Uzun and Ocak, 2019;Aydın et al, 2020) for the rangelands of Akdağ Mountains, Samsun, Türkiye (at nearly 1200 m above sea level). These rangelands, open to public grazing, has a climate in which summers are warm and humid, and winters are cool and damp (Aydin et al, 2019).…”
Section: Study Area and Weed Speciesmentioning
confidence: 99%
“…We determined that the ratio of species preferred and unpreferred was 70.5% and 29.5%, respectively, in mountainous rangelands (Akdağ) in Samsun, Türkiye. In that study, Aydın et al (2020) revealed that the other botanical families such as Asteraceae, Lamiaceae, Boraginaceae, Liliaceae, and Scrophulariaceae dominated most of the weed species that are preferred or somewhat preferred by ruminants. The high percentage of weed species may pose a risk to the quantity and quality of forages, livestock health, and the floristic patterns of the rangelands (Gutiérrez et al, 2008;Maduro Dias et al, 2020).…”
Section: Introductionmentioning
confidence: 97%